A concept for a distributed computer system for automation in industry. (4th August 2014) - Tomov, Pavel
In a contemporary computer–aided manufacturing environment the cost–effective, in the short term, and reliable operation of the distributed control systems is important. To fulfil this task a new concept is proposed here consisting of a method and tool.